1979
DOI: 10.1042/bj1810331
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and the role of rabbit testicular arysulphatase A in fertilization

Abstract: Arysulphatase A was purified from rabbit testis. The purification was accomplished by a four-step procedure involving (NH4)2SO4 fractionation, chromatography on DEAE-cellulose, SP(sulphopropyl)-Sephadex and affinity chromatography on concanavalin A-Sepharose. The specific activity of purified preparation was 135 mumol/min per mg of protein, which represented an increase of 900-fold above that of the crude homogenate. The purified enzyme (20-50 micrograms) was found to move electrophoretically as a single band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2

Year Published

1981
1981
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 44 publications
2
19
2
Order By: Relevance
“…However, it has been shown that the arylsulfatases are involved in the degradation of cerebroside sulfate esters, likely membrane components of most target cells. In this regard it is of interest that arylsulfatase from rabbit testes has been reported to disperse the cumulus of rabbit ova, thereby facilitating fertilization (27). The enzyme's role in the attenuation of anaphylaxis is well recognized (19), and a congenital absence of arylsulfatase is the cause for several human genetic disorders (28).…”
Section: -'mentioning
confidence: 99%
“…However, it has been shown that the arylsulfatases are involved in the degradation of cerebroside sulfate esters, likely membrane components of most target cells. In this regard it is of interest that arylsulfatase from rabbit testes has been reported to disperse the cumulus of rabbit ova, thereby facilitating fertilization (27). The enzyme's role in the attenuation of anaphylaxis is well recognized (19), and a congenital absence of arylsulfatase is the cause for several human genetic disorders (28).…”
Section: -'mentioning
confidence: 99%
“…The effect of neuraminidase upon the electrofocusing pattern of arylsulfatase B was monitored using Clostridium perfringens neuraminidase (Type VI) (Sigma Chemical Co., St. Louis, Mo.) (Farooqui and Srivastava, 1979).…”
Section: Enzyme Characterizationmentioning
confidence: 99%
“…Arylsulphatase activity was measured by following the release of p-nitrocatechol from p-nitrocatechol sulphate by incubating the enzyme with 10mM substrate in 0.25 M-sodium acetate buffer, pH 5.5, as described by Farooqui & Srivastava (1979). One unit of enzyme is defined as the amount liberating lumol of p-nitrocatechol/min.…”
Section: Assay Ofenzyme Activitymentioning
confidence: 99%
“…The dialysed solution was subjected to a concanavalin A-Sepharose column chromatography as described by Farooqui & Srivastava (1979). The fractions containing arylsulphatase were pooled, concentrated to 50ml on an Amicon cell (UM 10) and dialysed against 10vol.…”
Section: Assay Ofenzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation